PENGUJIAN USER EXPERIENCE PADA APLIKASI SMART HOME MENGGUNAKAN USE QUESTIONNAIRE - Muhammad Bambang Firdaus; Irfan Putra Pratama; Andi Tejawati; M Khairul Anam; Fadli Suandi (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2022)
This research was conducted to design an Android-based Smart Home application user interface that is easily understood by users to control the system and test the User Experience on the smart home application design. The data collection methods used were questionnaires, observations, and literature studies. For the system development method using the Linear Sequential Model / Waterfall Model method. Applications used in making designs and smart home applications include Android Studio, Sublime, Xampp, Adobe Xd, and Adobe Illustrator. The testing methods used include Usability testing and Usability Measurement using the USE Quistionnaire. This research produces a Smart Home application design that can be used by users to easily control the system.